Interdisciplinary design of a CO2 sensing system to face the pandemic within indoor spaces at Tecnológico de Costa Rica - Cordero-Picado, Kristel (2022)
During the COVID-19 pandemic facing the world, it became necessary to search for low-cost strategies to guarantee people’s health; while economic, educational, and social activities that were seriously affected are being reactivated. As research on the virus progresses, the relationship between the probability of transmission of COVID-19 and indoor air quality has been discovered, indicating that virus particles can accumulate easier in spaces where ventilation and air quality are deficient. This article describes the methodologies implemented from different disciplines for the design of a system, which is made up of a circuit, a casing, and a desktop application. The design of this system will allow the monitoring of air quality variables in the classrooms and laboratories of the Tecnológico de Costa Rica, by warning when spaces have poor air quality, and therefore the place must be ventilated.